Vitamin E and Provide Protective Effects Against Liver Injury Induced by HgCl: Role of CHOP, GPR87, and mTOR Proteins - Ahlam Alhusaini; Shahad Alghilani; Waad Alhuqbani; Iman H. Hasan (SAGE Publishing, 2021)
Background and Objective: Mercury is one of the most harmful heavy metals and its toxicity causes severe multi-organ dysfunction. This study was designed to explore novel molecular pathways involved in the hepatoprotective effect of vitamin E (Vit-E) and Lactobacillius plantarum (Lac-B) against mercury toxicity. Method: Acute hepatotoxicity was induced by administration of high dose of mercuric chloride (HgCl 2 ) in male rats, Vit-E or/and Lac-B were given along with HgCl 2 for 2 weeks. The effects of those antioxidants were studied focusing on their anti-apoptotic, anti-oxidative stress and anti-inflammatory eficacies. Histopathological examinations were also conducted. Results: The administration of HgCl 2 induced liver injury which manifested by elevation in serum ALT and AST. Liver MDA, caspase-3 and TNF-α levels were markedly increased; whereas, GSH level and SOD activity were declined. HgCl 2 significantly elevated the expressions of hepatic CHOP, GPR87, NF-κB and mTOR. Histopathological examination revealed massive hepatocyte degeneration following HgCl 2 administration. Treatment with Vit-E or/and Lac-B restored the normal levels of the previously mentioned parameters, as well as improved hepatic architecture. Conclusion: Vit-E and Lac-B provided protective effect against HgCl 2 -induced hepatotoxicity via reduction of oxidative stress and inflammation, and downregulation of CHOP, GPR87, NF-κB and mTOR proteins' expressions.